Investigation of binder distribution in graphite anodes for lithium-ion batteries - Müller, Marcus; Pfaffmann, Lukas; Jaiser, Stefan; Baunach, Michael; Trouillet, Vanessa; Scheiba, Frieder; Scharfer, Philip; Schabel, Wilhelm; Bauer, Werner (Journal of power sources, 2017)
Energy dispersive x-ray spectroscopy (EDS) is evaluated regarding its applicability for revealing the binder distribution in lithium-ion battery electrode films. Graphite anodes comprising carbon black and PVDF binder are subject to varying drying conditions during solvent removal in order to adjust different binder distributions; fluorine is used as a marker for the presence of PVDF. For electrodes of about 70 μm thickness the fluorine concentration is detected at the surface of the electrode film as well as at the interface between electrode film and current collector foil. It is clearly visible by EDS that increasing drying temperatures (and drying rates) result in an accumulation of binder at the surface and a corresponding depletion at the interface. It is demonstrated on the basis of ion-milled cross-sections of thick electrodes (ca. 400 μm) that a quantitative mapping of the binder distribution delivers additional information about concentration gradients in dependence of the drying parameters. [Display omitted] •Distribution of PVDF binder in graphite anodes is displayed by EDS-analysis.•Electrode's drying conditions strongly affect the binder distribution.•High drying rates result in binder accumulation at the electrode surface.